It's Not Just Welfare: Racial Inequality and the Local Provision of Public Goods in the United States. Issue 5 (September 2018) - An, Brian; Levy, Morris; Hero, Rodney
Recent research shows that inequality between racial groups is a critical determinant of redistributive policy in the United States. Using various measures of local and state spending and examining multiple levels of geographical and political jurisdictions, we extend this research to government spending on local public goods. Specifically, we examine (1) whether the extent to which income inequality falls along racial lines dampens local and state government spending on public goods, (2) which types of public goods are most affected by the racial structure of inequality, and (3) whether political variables such as local leaders' racial identities and party affiliation mediate the relationship between racial inequality and spending on public goods. The findings reaffirm the need to consider racial diversity and inequality jointly as influences on policy.